US Consumer Preferences for Home Lawn Fertilizers - Hayk Khachatryan; Alicia Rihn; Michael Dukes (EDIS)
Consumer preferences for home lawn fertilizers are not always informed and do not always align with best practices. Understanding the disconnect will help turf industry educators better address consumers’ misperceptions about fertilizers, and help industry stakeholders design more appealing products and educate consumers effectively as they promote them. Knowing consumer preferences greatly reduces stakeholders’ risks and improves efficiency in determining future product and promotional strategies. This 4-page report discusses the findings of a 2013 survey of 1,066 US homeowners about their preferences and willingness-to-pay for various lawn fertilizer attributes. Written by Hayk Khachatryan, Alicia Rihn, and Michael Dukes, and published by the Food and Resource Economics Department, November 2015.